Improving Creativity and Learning Outcomes Through Team-Assisted Individualization Learning Islamic Education Lessons - Abbas Lumbilsa; Asrori; Rusman (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
The purpose of this research is to improve the level of creativity and student learning outcomes of Islamic education. This study uses classroom action research to see the success of Team Assisted Individualization learning in increasing the creativity and learning outcomes of students in Islamic education in class VII (Junior High School) Wittayasansuksa School Songkhla Thailand. The research results can be seen from the increase in percentage, in the first cycle, the average student learning creativity is at a score of 42.50%, included in the (creative) category, while in the second cycle, the average student learning creativity has increased to reach a score of 47.50. % category (creative) and 30% category (very creative). Student learning outcomes have also increased. This can be seen from the percentage increase, in the first cycle, the average student learning outcomes were at a score of 25% (good) category, while in the second cycle, the average student learning outcomes experienced an increase in achieving a score by 60% category (good) and 25% category (Very Good).